Current observer-based critical conduction mode control of a bidirectional DC–DC converter in battery charging/discharging applications - Wan, Dai; Li, Jinliang; Zhang, Lulin; Xu, Jingtao (Frontiers in Energy Research, 2023)
A current observer-based digital critical conduction mode control of a bidirectional DC–DC converter with full-range soft switching for battery charging/discharging applications is proposed in this paper. Under the proposed control method, the bidirectional DC/DC converter operates in the critical continuous mode (CRM), the full-range zero-voltage switching (ZVS) can be achieved, and the inductor current ripple can be optimized. The CRM control is achieved by the proposed current observer, and the zero-crossing detection (ZCD) analog circuit or current sampling circuit can be eliminated. Therefore, compared with existing methods, the design complexity of the hardware circuit can be simplified. In addition, the proposed current observer can estimate the inductor current over a wide range of load and voltage variations. Therefore, the proposed control method can be applied to a wide range of charging and discharging applications. Finally, a prototype with 30–60 V input voltage, 24 V output voltage, and 75–150 kHz switching frequency is built. The experimental data and waveforms prove the correctness and advantages of the solutions proposed in this paper.